QTL Analysis and Fine Mapping of a Major QTL Conferring Kernel Size in Maize (Zea mays) - Wang, Guiying; Zhao, Yanming; Mao, Wenbo; Ma, Xiaojie; Su, Chengfu (Frontiers in Genetics, 2020)
Kernel size is an important agronomic trait for grain yield in maize. The objective of this study is to map QTLs and predict candidate genes for kernel size in maize. A total of 199 F2 and its F2:3 lines from the cross between SG5/SG7 were developed. Composite interval mapping (CIM) method was used for detecting QTLs in three environments of F2 and F2:3 populations. The result showed that a total of ten QTLs for kernel size were detected, among which five QTLs for kernel length (KL) and five QTLs for kernel width (KW). Two stable QTLs qKW-1 and qKL-2 were mapped in all three environments. In order to validate and fine map qKL-2, near isogenic lines (NILs) were developed by continuous backcross between SG5 (as the donor parent) and SG7 (as the recurrent parent). Marker assisted selection was conducted from BC2F1 generation with molecular markers near qKL-2. A secondary linkage map with six markers around the objective region was developed for fine mapping qKL-2. Finally, qKL-2 was mapped in a 1.95-Mb physical interval on maize chromosome 9 by blasting with Zea_Mays_B73 v4 genome. The results were confirmed with selected overlapping recombinant chromosomes. Transcriptome analyses showed that a total of 11 out of 40 protein coding genes differentially expressed between the two parents were detected in the identified interval . GRMZM2G006080 encoding a receptor-like protein kinase FERONIA, was predicted as a candidate gene to control kernel size. The work will not only help to understand the genetic mechanisms of kernel size of maize but also lay a foundation for further fine mapping and even cloning the promising loci.